AKTIVITAS ANTIBAKTERI EKSTRAK AIR KULIT BAWANG MERAH (Allium cepa L.) TERHADAP BAKTERI Propionibacterium acnes - Sa`adah, Hayatus; Supomo, Supomo; Musaenah, Musaenah (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Propionibacterium acnes is one of the causes of acne. Shallot peels contain flavonoids, tannins, and saponins which potentially have antibacterial activity. The purpose of this study was to determine whether the water extracts of shallot peels have antibacterial activity against Propionibacterium acnes and determine the concentration which can inhibit the growth of bacteria Propionibacterium acnes. This research is an experimental study. The research stage begins with the extraction of shallot peels using in the foundation. Antibacterial activity was tested using the diffusion method with the Cup-plate technique. Propionibacterium acnes used as a sample of bacteria, with extract concentrations of 5%, 10%, 20%, and 40%. Positive controls used are clindamycin 150 mg and negative controls were used dimethyl sulfoxide 1% (v / v). Data were analyzed with a statistical test of the Kolmogorov-Smirnov method. The measurement results inhibition zone of shallot peels water extract with a concentration of 5%, 10%, 20%, and 40% of the bacteria Propionibacterium acnes sequentially by 12.8 mm, 13 mm, 14.33 mm and 15.50 mm in the strong category. The measurements of bacterial growth inhibition zone were statistically analyzed with the Kruskal-Wallis method gained 0,053 results indicating that the test has a significant effect (P > 0.05) with a decision that means that there is no significant difference between all concentrations.